Academic self-efficacy and vocational maturity in college students - Saavedra, Liliana Rodríguez; Zamata, Paulina Marisol Camargo; López, Roberto Martín Gamarra; Pilco, Rocío Yvonne Taboada; Miñano, Celina Elizabeth Rodríguez (CENTRAL ASIA AND THE CAUCASUS, 2022)
During the beginning of the pandemic, many university students in the nursing profession faced various uncertainties, among them doubting whether to continue studying a professional career that would demand risks to their health, but despite this there is a noble vocational feeling of patient care, which kept them determined to continue studying and achieve their goals. In addition to the whole context in which the health system and the population found themselves, these two constructs became determinants for persistence and continuity of studies. Academic self-efficacy is understood as students' perception of their own abilities to initiate, solve, and successfully complete assigned tasks. Vocational maturity is the association of skills that people must face in vocational tasks. The present research studies these two variables in university students at a private university in Lima, Peru. The objectives were a) to identify the association between self-efficacy and vocational maturity and b) to establish the differences between self-efficacy and vocational maturity in first and fifth year nursing students. Methods: Quantitative approach, comparative descriptive level, basic, substantive, correlational and non-experimental des ign. We worked with a sample of 190 nursing students, of which 90 participants belong to the first year of studies and 100 participants belong to the fifth year of studies. The instruments used to collect the information were: the vocational maturity questionnaire (Rodriguez, 2015) and the Self-Efficacy scale (Bueno et al., 2018). The results of the study showed that self-efficacy presents a moderate significant relationship with vocational maturity, concluding that the greater the vocational maturity, the greater the feeling of self- efficacy. Likewise, students in their fifth year of studies have higher levels of self- efficacy and vocational maturity than first-year students.